Simultaneous central nervous system complications of C. neoformans infection - Alejandra Gonzalez Duarte; Jesus Higuera; Vicente Gijon-Mitre; Guillermo García Ramos (MDPI AG, 2009)
The most common neurological manifestation of Cryptococcus neoformans infection is meningitis. Other less common manifestations include parenchymal central nervous system (CNS) granulomatous disease, hydrocephalus and stroke. C. neoformans is often suspected in immunodepressed patients, but it can be easily overlooked in otherwise healthy patients. This paper provides a detailed clinical description of a patient without immunosupression who developed multiple simultaneous neurological manifestations after the infection with C. neoformans.